Competências empreendedoras e Base Nacional Comum Curricular: uma reflexão sobre a formação de professores para a educação empreendedora - Carvalho, Fabiana Vicente de (2022)
This study is part of the New Technologies in Education Research Line of the Graduate Program in Education: Curriculum of the Pontifical Catholic University of São Paulo. Its objective is to bring a reflection on the training of teachers to work on entrepreneurial skills in an articulated way with the skills indicated in the National Common Curriculum Base from the courses "Entrepreneurial Skills Integrated to the BNCC for Educators" offered in the EAD modality. It has a qualitative approach. To deepen the theme, the methodological foundation brought a theoretical reference on Curriculum by competence, Entrepreneurship, Entrepreneurial Education and the training of teachers in the EAD modality. The teaching cases delivered by the educators were analyzed in order to search the articulation between the two matrices in the pedagogical practices reported. In the survey, it was identified that it is possible to work the two matrices in an articulated way and that educators have an easier time in recognizing some competences than others